7-α-O-Methylmorroniside ameliorated brain injury in 5×FAD mice by regulating the gut microbiome and NMDAR2B - Hao, Fengxiao; Zeng, Mengnan; Cao, Bing; Liang, Xiwen; Hao, Zhiyou; Ye, Kaili; Jiao, Xinmian; Feng, Weisheng; Zheng, Xiaoke (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive decline. 7-α-O-Methylmorroniside (MorA), an iridoid glycoside extracted from Cornus officinalis Sieb. et Zucc., has been shown to have neuroprotective effects, but the mechanism of its anti-AD effect has not been clarified. In the present study, we investigated the mechanism by which MorA ameliorated brain injury in 5×FAD mice by using gut microbiota (GM) combined with in vitro and in vivo pharmacological experiments. Behavioral tests revealed that MorA could enhance learning and memory ability and improve cognitive impairment. The results of pathology, flow cytometry and biochemical indexes showed that MorA could reduce the levels of neuronal apoptosis, oxidative stress, Aβ1-40, Aβ1-42, p-Tau, and inflammatory factors in the mouse brain tissues, and improve brain damage. 16S rDNA sequencing showed that MorA increased the abundance of the beneficial bacterium Lactobacillus and decreased the abundance of the inflammation-associated Muribaculaceae and Prevotellaceae, and that these differential bacteria were closely associated with brain biochemical indicators. In addition, pathway enrichment analysis, Western blot and molecular docking results showed that the ameliorative effect of MorA on brain injury in 5×FAD mice was closely related to NMDAR2B. Next, an inhibitor of NMDAR2B was added to Aβ25-35-induced N9 and PC12 cells to further investigate whether the effect of MorA on AD was mediated through NMDAR2B. In conclusion, MorA ameliorated brain injury in 5×FAD mice by restoring GM homeostasis and inhibiting NMDAR2B.